POLA RENANG DAN GERAKAN IKAN KARANG DI SEKITAR RUMPON DAN BUBU - Fonny J.L. Risamasu; Mulyono S. Baskoro; M. Fedi A. Sondita; Dedi Soedharma (Buletin PSP, 2007)
This paper describes swimming and movement patterns of some reef fishes around some fish aggregating devices (FADs) and some traps deployed in Hansisi waters, Semau, Kupang. There were 62 species of reef fishes observed around the FADs and 47 species around the fish traps. The distances between the reef fishes from the FADs and between the fishes and the traps were commonly between 1-2 m. Around the FADs, the swimming patterns of the fishes commonly observed included soliter (36 species), front approach (56 species or 90%), up-down movement (28 species or 45%), above the FADs (24 species or 39%) and beside the FADs (24 species or 39%). Around the traps, the swimming patterns observed were soliter (26 species) while movement patters observed were front approach (37 species or 79%), up-down movement (24 species or 50%), above the traps (21 species or 45%) and beside the traps (30 species or 64%). These patterns of fish swimming and movement determined effectivness of the FADs as fish attractor and traps as capture devices.